Characterıstıc Propertıes Of Indıvıduals Wıth Deep Bıte And Treatment Approaches In Early Perıod - Meliha Rübendüz; Elçin Esenlik (Galenos Yayinevi, 2002)
Deep bites are encountered among malocclusions very often and it is very difficult to treat them successfully. They are found on 10% of the population and we are commonly faced in combination with anomalies in the direction of antero-posterior of maxilla and mandibula. Craniofacial morphology together with dental factors such as incisor angles, canine position, infraocclusions of molars, molar tubercules heights can effect the growth of deep bite. These symptoms are often revealed in early stages and show an increasing trend in puberlul stage (1). Craniofacial growth model and the symptoms of this model play the most important role to estimate how the individual may answer the treatment. Removable, functional and orthopedic appliances, designed in various shapes, can be used in the early deep bite treatments. The effects of these appliances on dental movements, skeletal change and growth models are different. The determination of specific treatment way, period and time for each individual is very important for the stabilization of the results. Growth model, functional factors and the development of dentoalveoler structures should be evaluated precisely in order to make an effective diagnosis and treatment plan. In this article, dentofacial structures of individuals showing short face syndromes with deep bite will be identified and interventions in early stages will be analyzed. In addition, a case treated in the early period of developmental stage will be presented in this article .